Health monitoring of floating structure by utilizing support vector machines - Tabata, Akihisa (International Journal of Engineering and Technology, 2016)
We explored the damage detection method for a floating structure by utilizing the natural ocean waves for the floating body. And we utilized the discrete Fourier transform as well as the learning and judgment functions of the support vector machines. It showed a possibility that it can perform the health diagnosis for the floating structure even using the strain response vibrations by inputting the natural waves with different cycles and wave heights.